Plasmodium berghei-Released Factor, PbTIP, Modulates the Host Innate Immune Responses - Kalia, Inderjeet; Anand, Rajesh; Quadiri, Afshana; Bhattacharya, Shreya; Sahoo, Bijayalaxmi; Singh, Agam Prasad (Frontiers in Immunology, 2021)
The Plasmodium parasite has to cross various immunological barriers for successful infection. Parasite have evolved mechanisms to evade host immune responses which hugely contribute to the successful infection and transmission by parasite. One way in which the parasite evades immune surveillance is by expressing molecular mimics of host molecules to manipulate the host responses. In this study, we report a Plasmodium berghei hypothetical protein PbTIP (PbANKA_124360.0) which is a Plasmodium homologue of the human T cell immunomodulatory protein (TIP). The later possess the immunomodulatory activities and suppressed the host immune responses in a mouse acute graft-versus-host disease (GvHD) model. The Plasmodium berghei protein, PbTIP, is expressed on the merozoites surface and exported to host erythrocytes surface upon infection. It is shed in the blood circulation by the activity of an uncharacterized membrane protease(s). The shed PbTIP could be detected in the host serum during infection. Our results demonstrate that the shed PbTIP exhibits binding on the surface of macrophages and reduces their inflammatory cytokines response while up-regulating the anti-inflammatory cytokines such as TGF-β and IL-10. Such manipulated immune responses are observed in the later stage of malaria infection. PbTIP induced Th2 type gene trancript changes in macrophages hints towards its potential to regulate host immune responses against the parasite. Therefore, this study highlights the role of a Plasmodium released protein PbTIP in immune evasion using the macrophages and may represent the critical strategy of the parasite to successfully survive and thrive in its host. This study also indicates at the human malaria parasiteTIP as a potential diagnostic molecule which could be exploited in the lateral flow based immunochromatographic tests for malaria disease diagnosis.